2001
DOI: 10.1080/152873901300018093
|View full text |Cite
|
Sign up to set email alerts
|

Lead Accumulation in Human Ovarian Follicular Fluid, and in Vitro Effect of Lead on Progesterone Production by Cultured Human Ovarian Granulosa Cells

Abstract: Lead content of ovarian follicular fluid obtained from 23 women was determined by atomic absorption spectrophotometry. In an in vitro experiment the direct effect of lead on the morphology and on progesterone (P) production by cultured granulosa cells of six women was investigated. Follicular fluid and granulosa cells were obtained from follicular aspirates of women undergoing in vitro fertilization (IVF) and embryo transfer (ET). Granulosa cells were cultured for 48 h to form monolayers in the presence or abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
2
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 17 publications
0
15
2
4
Order By: Relevance
“…The FF concentrations of Hg, Cd and Pb measured in our study are generally lower than reported in the literature [7,12,16,[21][22][23]], a comprehensive comparison of which is provided elsewhere [25]. The lower FF values measured in our study may reflect the highly sensitive ICP-MS method employed, coupled to different exposure patterns.…”
Section: Associations Among Metals In Ff Blood and Urine Compartmentscontrasting
confidence: 60%
See 1 more Smart Citation
“…The FF concentrations of Hg, Cd and Pb measured in our study are generally lower than reported in the literature [7,12,16,[21][22][23]], a comprehensive comparison of which is provided elsewhere [25]. The lower FF values measured in our study may reflect the highly sensitive ICP-MS method employed, coupled to different exposure patterns.…”
Section: Associations Among Metals In Ff Blood and Urine Compartmentscontrasting
confidence: 60%
“…It is presumed that FF will provide a closer approximation to the biologically-effective dose of a toxicant to an oocyte than achieved using blood or urine measures. Several groups previously reported Hg, Cd and/or Pb concentrations measured in human FF specimens, although with little methodologic detail [7,12,15,[21][22][23]24]. To facilitate investigation of associations between toxic metals in FF and IVF outcomes, our laboratory recently developed and validated a method for the measurement of elements in FF at trace concentrations [25].…”
Section: Introductionmentioning
confidence: 99%
“…Despite their suspected impact on female reproduction and environmental prevalence (1)(2)(3)(4)(5), the concentration of these elements within the follicular fluid (FF) has not been well characterized. In an earlier study our group focused on the influence of lead concentration in FF on the outcome of pregnancy.…”
mentioning
confidence: 99%
“…All three metals have been identified in human follicular fluid (Zenzes et al, 1995;Paksy et al, 2001;Al-Saleh et al, 2008) and ovarian tissue (Varga et al, 1993), and have been associated with adverse reproductive outcomes in epidemiologic studies. While the biological mechanisms by which these metals may exert adverse reproductive effects have not been fully elucidated, toxicologic studies have provided some insights.…”
Section: Introductionmentioning
confidence: 99%